2021
DOI: 10.1371/journal.pone.0253108
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and mitigation strategies among homeless shelter workers at risk of COVID-19

Abstract: Objective To describe the work environment and COVID-19 mitigation measures for homeless shelter workers and assess occupational risk factors for COVID-19. Methods Between June 9-August 10, 2020, we conducted a self-administered survey among homeless shelter workers in Washington, Massachusetts, Utah, Maryland, and Georgia. We calculated frequencies for work environment, personal protective equipment use, and SARS-CoV-2 testing history. We used generalized linear models to produce unadjusted prevalence ratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…As a result, numerous healthcare providers either left their jobs or were fired for going against hospital policy. 26 , 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, numerous healthcare providers either left their jobs or were fired for going against hospital policy. 26 , 27…”
Section: Discussionmentioning
confidence: 99%
“…As a result, numerous healthcare providers either left their jobs or were fired for going against hospital policy. 26,27 These challenges in obtaining and receiving authorization to access PPE during the early days of the pandemic affected providers in GPD and HPACT programs. One GPD leader took it upon himself to purchase a sewing machine to produce masks for staff and Veteran clients.…”
Section: Maintaining Clinician Confidence Through Preparedness Planningmentioning
confidence: 99%
“…Previous literature has found that lack of guidance, insu cient training, and di culty obtaining infection control supplies were barriers to implementing infection control measures in homeless shelters and other community settings [4,5,9]. Homeless shelter staff and health care providers have also described sta ng constraints as barriers to infection prevention and control [10,11]. However, little is known about WASH practices in shelters serving PEH in general and during infectious disease outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, data from public health surveillance and field investigations, as well as anecdotal evidence from media reports, have suggested that certain worker groups experience increased risk of contracting COVID‐19 due to their work. Epidemiologic evidence points to occupational acquisition of COVID‐19 among healthcare personnel 2–5 and case clusters have been associated with various workplaces including hospitals, 6 long‐term care facilities, 7,8 correctional facilities, 9,10 homeless shelters, 11,12 and meat and seafood processing plants 13–17 . This evidence implies that transmission of SARS‐CoV‐2 occurs in the workplace and that workers in certain occupations or industries could be at increased risk for infection.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence implies that transmission of SARS‐CoV‐2 occurs in the workplace and that workers in certain occupations or industries could be at increased risk for infection. Factors suspected to be associated with increased risk of occupational acquisition of COVID‐19 include close contact with COVID‐19 patients in healthcare settings; working in close proximity with coworkers, customers, or the public, especially for prolonged periods; working in densely populated, enclosed, or poorly ventilated workplaces; and the requirement for in‐person work 2–17 …”
Section: Introductionmentioning
confidence: 99%